تحديد الخواص الميكانيكية للصلب الكربوني(الصلادة، قوة الشد، الاستطالة) لا إتلافياًNon-Destructive)) باستخدام تقنية الأمواج فوق الصوتية(Ultrasonic) - محمد محمد أحمد (Latakia University Journal -Engineering Sciences Series, 2019)
إن تقنية الأمواج فوق الصوتية للتأكد من سلامة المسبوكات والمنتجات المصنعة بالحدادة واللحام وخلوها من العيوب الداخلية، مستخدمة على نطاق واسع كأسلوب فحص لا إتلافي يعتمد عليه [1] [2]. ونظرا للإمكانيات غير المحدودة لهذه التقنية فقد أخذت استخداماتها بالتزايد وخاصة في دراسة خواص المواد الهندسية لا إتلافيا في السنوات الأخيرة [3]. وقد تم في هذا البحث دراسة إمكانية إيجاد العلاقة بين سعة إشارة الصدى للأمواج فوق الصوتية المنعكسة عن الجدار المقابل لسطح العينة وبعض الصفات الميكانيكية الشائعة والهامة كالصلادة، وقوة الشد، ونسبة الاستطالة لعينات من الصلب الكربوني بسماكات مختلفة وبنى ميكروسكوبية متنوعة. حيث تبين أنه بزيادة السماكة تقل سعة إشارة الصدى للأمواج المنعكسة مع ثبات التردد. بالإضافة إلى ذلك لوحظ أن إشارة الصدى تخضع لمتغيرات يمكن قياسها عندما تتفاعل مع بنية المادة المتغيرة تبعاَ للمعالجة الحرارية المتبعة، وهكذا نستطيع الربط بين الخصائص الميكانيكية والخصائص فوق الصوتية بشكل بياني أو بمعادلات تجريبية. على الرغم من أن هذه الطريقة تعتبر من الطرق التقريبية إلا أنها تمتاز بدقة عالية للأغراض الهندسية. The use of ultrasonic as a non-destructive method is usually understood to be an inspection of castings, forging and welds, for internal defects. However, ultrasonic, can be used for other kinds of qualitative evaluations, for example assessment of physical, mechanical and structural properties. In this paper, pulse echo amplitude attenuation method with respect to sound traveling distance have been used as one technique of microstructure and mechanical properties of metals. The technique involves measurements of either ultrasonic velocity or attenuation through the metals. In this article an attempt has been made to correlate echo amplitude response of both amplitude height and amplitude attenuation with selected common mechanical properties such as hardness, tensile strength and elongation of different heat- treated conditions of high carbon steel. The ultrasonic approach is based on how waves are influenced when they are propagated within the material being tested. These waves undergo changes which can be measured and the material can be evaluated accordingly. The evaluation of properties of the material can then follow indirectly, by means of graphical or empirical correlation. Hence on can interpret certain changes in the ultrasonic signal as a change in the structure of the material.